Micropulse laser trabeculoplasty for uncontrolled open angle glaucoma in Peruvian patients - Cornejo,Diego Valera (2018)
ABSTRACT Objective: We describe the pressure lowering effect of micropulse laser trabeculoplasty (MLT) in patients with uncontrolled open angle glaucoma (OAG). Design: Retrospective case series. Methods: We retrospective reviewed 30 eyes with Open angle Glaucoma (OAG) at the Vista Clinic in Lima, Peru. A single session of MLT treatment was delivered using a 532 nm Frequency doubled Nd. YAG laser to 360º of the trabecular meshwork with a power of 1000 mW, 25 % of duty cycle, and 300 ms. of exposure. The intraocular pressure (IOP) was measured at baseline and at 1 day, 1 week, 3, 6 months post-treatment and were followed up for one last control. Results: The mean baseline IOP was 15.6 mmHg and in the last control was12.8 mmHg, mean follow up time of 19 months (+/- 10 SD). The mean reduction of IOP in the first day was 1.6 mmHg (± 2.6 SD) and 1.2 mmHg (± 3.3 SD) in the last follow up. The mean percentage of IOP reduction was 17.9% and 7 eyes (40%) had IOP reduction greater than 20%. No statistical difference in relation to demographics characteristics of the patients. The greatest reduction was achieved in the first day with a median of 2.00 (P 0.001). A tendency to achieve higher reduction of IOP in patients with higher baseline IOP was found, but was not statistical significant. No adverse reactions occurred. Conclusions: Micropulse laser trabeculoplasty can temporarily be effective in reducing the IOP in some patients with uncontrolled Open angle glaucoma and appears to be safe.